Sweet surfactants: packing parameter-invariant amphiphiles as emulsifiers and capping agents for morphology control of inorganic particles. Issue 35 (22nd August 2018) - Voggel, Michael; Meinusch, Rebecca M.; Siewert, Vanessa; Kunkel, Marius; Wittmann, Valentin; Polarz, Sebastian
Abstract : Exploration of isomer effects on amphiphile properties ( e.g. emulsification and as nanoparticle growth modifiers) using a library of glycoside-based surfactants. Abstract : Surfactants are not only pivotal constituents in any biological organism in the form of phospholipids, they are also essential for numerous applications benefiting from a large, internal surface, such as in detergents, for emulsification purposes, phase transfer catalysis or even nanoparticle stabilization. A particularly interesting, green class of surfactants contains glycoside head groups. Considering the variability of glycosides, a large number of surfactant isomers become accessible. According to established models in surfactant science such as the packing parameter or the hydrophilic lipophilic balance (HLB), they do not differ from each other and should, thus, have similar properties. Here, we present the preparation of a systematic set of glycoside surfactants and in particular isomers. We investigate to which extent they differ in several key features such as critical aggregation concentration, thermodynamic parameters, etc. Analytical methods like isothermal titration calorimetry (ITC), tensiometry, dynamic light scattering (DLS), small angle-X-ray scattering (SAXS), transmission electron microscopy (TEM) and others were applied. It was found that glycosurfactant isomers vary in their emulsification properties by up to two orders of magnitude. Finally, we have investigated the role of the surfactants in a microemulsion-based technique for the generation of zinc oxide (ZnO) nanoparticles. We found that the choice of the carbohydrate head has a marked effect on the shape of the formed inorganic nanocrystals.